Tanggung Jawab Bank Terhadap Hilangnya Dana Nasabah Penyimpan - Umarella, Fathin Luqyana; Tjoanda, Merry; Haliwela, Nancy Silvana (Faculty of Law Universitas Pattimura, 2025)
The form of a bank's obligations to its customers must be linked to the issue of legal protection of the bank, so the form of the bank's responsibility cannot be separated from the provisions of laws and regulations. If a customer loses money or savings, the bank is required to provide compensation to the customer who lost their money. The type of research used is normative juridical, conducted by studying legal principles, concepts, and regulations. The research method used refers to primary, secondary, and tertiary legal materials with a legislative approach and a conceptual approach, as well as using library research. The analysis of regulatory materials is conducted from the perspective of the applicable provisions. The results of this study indicate that legal protection for customers' deposit funds in banks as consumers can be viewed in Law Number 8 of 1999 concerning Consumer Protection, which stipulates the obligation of banks to comply with the procedures for creating standard clauses, as outlined in PBI Number: 7/6/PBI/2005 concerning Transparency of Banking Products and the Financial Services Authority Regulation Number: 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector. The responsibility of conducting business activities between banks and customers creates two sides of responsibility, namely the obligations of the bank itself and the obligations to the customers who deposit funds as a result of the legal relationship. The relationship between customers and banks involves the bank's obligation to handle customer complaints, including resolving them within the established timeframe. The responsibility of each party to maintain the confidentiality of the bank must be carefully observed so that both parties can avoid potential issues that may arise between the bank and its customers.